Comparative toxicity of pristine graphene oxide and its carboxyl, imidazole or polyethylene glycol functionalized products to Daphnia magna: A two generation study. (June 2018) - Liu, Yingying; Han, Wenli; Xu, Zhizhen; Fan, Wenhong; Peng, Weihua; Luo, Shenglian
Abstract: To investigate the chronic toxicity of graphene oxide (GO) and its functionalized products (GO-carboxyl, GO-imidazole and GO-polyethylene glycol), a two-generation study was conducted using the aquatic model species Daphnia magna . Each generation of daphnids were exposed for 21 days to 1.0 mg L −1 graphene material, with body length, neonate number, time of first brood and the intrinsic rate of natural increase (r) assessed as endpoints. Chronic exposure to GO, GO-carboxyl, and GO-imidazole had no adverse effect on body length or offspring number in the daphnid F0 generation, however, this exposure paradigm led to significant growth or reproduction inhibition in the following generation. Meanwhile, GO was found to show the strongest inhibitory effect, sequentially followed by GO-carboxyl and GO-imidazole. With exposure to GO-polyethylene glycol, no significant effects on growth or reproduction were observed for both F0 and F1 generation daphnids. These results reveal that carboxyl, imidazole and polyethylene glycol functional attachments alleviate the bio-toxicity of GO, especially polyethylene glycol. The increased C/O atomic ratio present in GO-carboxyl, GO-imidazole and GO-polyethylene glycol due to functionalization may mainly explain the reduced toxicity. Graphical abstract: Image 1 Highlights: The chronic toxicity of GO and its functionalized derivatives to aquatic organisms was compared. GO showed the strongest inhibitory effect on daphnid growth and reproduction, followed by GO-carboxyl and GO-imidazole. GO-polyethylene glycol did not influence the growth and reproduction of daphnids. The toxicity of GO, GO-carboxyl, GO-imidazole and GO-polyethylene glycol to Daphnia magna is C/O atomic ratio dependent. Abstract : GO, GO-carboxyl, GO-imidazole and GO-polyethylene glycol inhibit the survival, growth and reproduction of Daphnia magna in a C/O atomic ratio dependent manner.